Ultrasound guided truncal blocks for post operative analgesia – A study of 100 cases for the first time in Bangladesh - NA, Khanum; MSB, Muhit; NC, Ahmed; LD, Haque; KE, Ibrahim; NF, Amin (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Ultrasound guided (USG) nerve block techniques have been used for post operative analgesia for truncal operations to limit the perioperative use of NSAID and opioids. USG visualization offers safe blocks by optimal needle positioning, direct visualization of peripheral nerves and local anesthetic distribution. In Bangladesh, first ultrasound guided nerve block studies were started in the Dept. of Anesthesia, Analgesia and ICU of Bangladesh Medical College hospital. This Study has been carried out in the operation theatre and post operative room. Ultrasound guided Rectus sheath block, Subcostal TAP block, Classical TAP block, Ilio inguinal and Ilio hypogastric nerve block provide post operative analgesia of the abdominal wall. PEC 1, PEC 2 and Serratus Anterior plain block provide post operative analgesia for anterior chest wall. This study was done with 100 patients coming for abdominal surgeries and anterior chest wall surgeries. These blocks were given after induction and before giving incision in case of general anesthesia or after operation in case of spinal anesthesia. This study is an audit of ultrasound guided nerve blocks in terms of analgesia score, patient satisfaction, outcome of anesthesia and complications. Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 29-31